Globalization:Its Effects and Implications for Technical Education - Tulsi, P. K. (Journal of Engineering Education Transformations, 1999)
Indian economy after remaining protected for more than forty years plunged into drastic economic reforms in 1991, when a balance of payment crisis sent the national government in search of aid from IMF.